PENGGUNAAN METAFORA TUBUH PEREMPUAN DALAM KITAB HOSEA - Asnath N Natar (Jurnal Ledalero, 2016)
In a partriarchal society the what and the how of women and her body, is largely decided upon by males rather than by women themselves. Not infrequently a woman’s body is used to depict something negative, which not only results in no respect for a woman’s body, but can lead to violence against her. The Book of Hosea is a book that uses the woman and her body as a metaphor of the relationship between God and the people of Israel, where the woman and her body are depicted negatively. This article criticises the use of the woman and her body in the relationship between God and God’s people, and its impact on the husband-wife relationship.